Comparison of different software solutions for AVC quantification using contrast enhanced MDCT. (4th February 2022) - Evertz, R; Hub, S; Backhaus, S; Lange, T; Toischer, K; Kowallick, J; Hasenfuss, G; Schuster, A
Abstract: Funding Acknowledgements: Type of funding sources: None. Aims: Estimating aortic valve calcification (AVC) derived from multi detector computed tomography (MDCT) scans in aortic stenosis (AS) patients has gained increasing interest for diagnostic and prognostic reasons. Little is known about the interchangeability of AVC obtained from different software solutions which, was systematically determined in consecutive patients undergoing contrast enhanced MDCT before TAVR. Methods and results: 50 randomly selected patients who underwent contrast enhanced MDCT for TAVR planning were included in the analysis. All MDCT data sets were analysed using three different software vendors (3 Mensio, CVI 42, Snygo.Via). AVC score was expressed as mm³. For analysing intra- and inter-observer variability a subset of 10 patients were analysed twice with at least 2 weeks in between the measurements. Intra- and inter-observer variability was quantified using the ICC reliability method, Bland-Altman analysis and coefficients of variation. AVC scores were successfully obtained using all software solutions (3 Mensio 941 ± 623, CVI42 941 ± 637, Syngo.Via 948 mm³ ± 655) without significant differences (p = 0.455). There was excellent intra- (3 Mensio: ICC 0.999 [0.995 – 1.000], COV 3.86 %, mean difference -19.28 [± 45.07]; CVI 42: ICC 1.000 [0.999 – 1.000], COV 1.6 %, mean difference -10.28 [± 18.6]; Syngo.Via: ICC 0.998 [0.993 – 1.000], COV 4.13 %, mean difference -24.81 [± 48.52]) and inter-observer variability (3 Mensio: ICC 1.000 [0.999 – 1.000], COV 1.38 %, mean difference -7.14 [± 16.20]; CVI 42: ICC 1.000 [1.000 – 1.000], COV 1.01 %, mean difference -1.74 [± 11.83]; Syngo.Via: ICC 0.996 [0.985 – 0.999], COV 6.68 %, mean difference -0.65 [± 79.43]) for all software types. Best inter-vendor agreement was found between CVI 42 and Syngo.Via (ICC 0.997 [CI 0.995-0.998], COV 7.26 %, mean difference -7 [± 68.60]) followed by 3 Mensio / CVI 42 (ICC 0, 996 [CI 0, 922-0, 998], COV 8.95 %, mean difference -0.06 [± 84.16]) and 3 Mensio / Syngo.Via (ICC 0, 992 [CI 0, 986-0, 995], COV 12.19%, mean difference -7.06 [± 115.07]). Conclusion: Contrast enhanced MDCT derived AVC scores are interchangeable between and reproducible within different commercially available software solutions. This is important since sufficient reproducibility, inter-changeability and valid results represent prerequisites for accurate TAVR planning and wide spread clinical use.